ARID1A Variations in Cholangiocarcinoma: Clinical Significances and Molecular Mechanisms - Zhao, Shankun; Xu, Youwen; Wu, Weizhou; Wang, Pan; Wang, Yichao; Jiang, Hao; Zhu, Jie (Frontiers in Oncology, 2021)
Cholangiocarcinoma (CCA), a high mortality malignant carcinoma characterized by advanced disease and frequent recurrence, constitutes a major challenge for treatment and prognosis. AT-rich interaction domain 1A (ARID1A) variation is a distinct genetic entity in CCA, getting mounting concerns recently. Here, we comprehensively reviewed the clinical significance and molecular mechanisms of ARID1A alterations in CCA. Based on the independent data derived from 29 relevant studies, the variation rate of ARID1A in intrahepatic and extrahepatic CCA is reported at 6.9%-68.2% and 5%-55%, respectively. Most of the included studies (28/29, 96.6%) suggest that ARID1A serves as a tumor suppressor in CCA. ARID1A variation may be an important prognostic indicator to predict disease mortality, metastasis, and recurrence in patients with CCA. Multifactorial molecular mechanisms are involved in the relationship between ARID1A variations and the pathogenesis and pathophysiology of CCA, including disruption of the cell cycle, chromatin remodeling, oxidative stress damage, DNA hypermethylation, and the interaction of multiple genes being affected. This review describes that ARID1A variation might be a potential diagnostic and prognostic biomarker for CCA. Future diagnoses and treatments targeting ARID1A hint towards a precision medicine strategy in the management of CCA.